Pentaarylazafullerenes and their triaryldihydro and tetraarylmonohydro precursors - Neubauer, Ralf; Heinemann, Frank Wilhelm; Hampel, Frank; Rubin, Yves; Hirsch, Andreas (Angewandte Chemie International Edition, 2012)
Give me five! The title compounds were isolated from the acid-catalyzed reaction of a CN precursor with electron-rich aromatic compounds. Single-crystal X-ray diffraction on two compounds reveals characteristic packing motifs; the triaryldihydro derivative has a pseudo-stacked arrangement (Cviolet/yellow, Nblue, Ored, Hwhite). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.